TUJUAN, ASAS DAN KARAKTERISTIK PEMELIHARAAN - Fatimah Azzahra; Nadya Ayu Agustin; Marcelya Widia Putri (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2024)
Organizational commitment is a psychological bond between employees in anorganization that is characterized by strong trust and acceptance of organizationalgoals and values, a willingness to seek to achieve organizational interests, and astrong desire to maintain their position as members of the organization. Aspects oforganizational commitment: (a) affective commitment (b) normative commitment,(c) continuous commitment. Ways that can be done to build organizationalcommitment: (a) Make it charismatic, (b) Build the tradition, (c) Provide extensivetwo-way communication, (d) Create a sense of community, (e) Build value-basedhomogeneity , (f) Support employee development, (g) Commit to actualizing, (h)Provide first-year job collenge, (i) Provide developmental activities, (j) Commit topeople-first values, (k) Hire